Vegetation Restoration Alters Fungal Community Composition and Functional Groups in a Desert Ecosystem - Zhang, Ying; Cao, Hongyu; Zhao, Peishan; Wei, Xiaoshuai; Ding, Guodong; Gao, Guanglei; Shi, Mingchang (Frontiers in Environmental Science, 2021)
Revegetation is regarded as an effective means to improve the ecological environment in deserts and profoundly influences the potential ecological functions of the soil fungal community. Therefore, Illumina high-throughput sequencing was performed to characterize the soil fungal diversity and community composition at two soil depths (0–10 cm and 10–20 cm) with four revegetation durations (natural grassland, half-mature, nearly mature, and mature Pinus. sylvestris var. mongolica plantations) in the Mu Us Sandy Land, China. The effects of soil properties on soil fungal communities were also examined to reveal the connection between fungal function and soil environment. The results indicated that 1) soil nutrient content and enzyme activity showed significant differences through the restoration durations, 2) there was no significant effect of soil depth on soil fungal diversity, while the Shannon diversity index of all fungal communities was significantly different among different revegetation durations, 3) compared with grassland, ectomycorrhizal fungi (notably, Inocybe, Tuber, and Calostoma) were abundant in plantations. The endophyte fungus Mortierella was among the top 10 genera in all soil samples and arbuscular mycorrhizal fungus Diversispora was the indicator genus of the grassland, and 4) catalase and total nitrogen were the main factors affecting fungal community composition and were closely related to saprotrophs and pathotrophs, respectively. This new information indicates the variation of soil fungal communities along revegetation durations and highlights the interaction between fungal functions and desert ecosystems.